Evaluasi Keberhasilan Tanaman Revegetasi Lahan Pasca Tambang Batubara Pada Blok M1W PT Jorong Barutama Greston, Kalimantan Selatan - Omo Rusdiana; Adi Setiadi (Jurnal Silvikultur Tropika, 2019)
Reclamation activities should be carried out after mining operation for restoring and improving the function of the land to be in better condition and productive (P.60/Menhut-II/2009). This research aims to analyze the status of the success of revegetation, based on growth ability and performance of A. mangium plants at PT Jorong Barutama Greston Block M1W; to recommend improvements for the land and plants; and to identify the cause of revegetation failure. The results of this research indicated that status of the revegetation success at Block M1W have not been categorized as successful category. The success rate were considered from the average growth percentage and health level of plants which were less than 60% (score 1, bad performance), namely 59.38% and 50.01% respectively. The improvement that could be done were soil amendment and the use of plants which are resistant to poor environment. The plants have to be resistant to acid soil and high content of heavy metal. The main causes of revegetation failure were site condition which were not conducive for A. mangium plant growth and lack of plant maintenance. This was the cause of bad plant growth performance. Besides that, Standard Operational Procedure (SOP) on revegetation activities need to be improved and plant maintenance should be enhanced, particularly those related with pest and disease control.Key words: A. mangium, evaluation, post coal mining, revegetation